PSYCHOLOGICAL ANALYSIS OF CREATIVITY IN ADOLESCENTS - BABAJANOVA FOTIMA FARMANOVNA (International Journal of Psychosocial Rehabilitation, 2020)
This article proves that the factors influencing the creative characteristics of adolescents, the transfer of intellectual activity to new conditions, the compatibility of the general intellectual components of adolescence with the characteristics of creativity have their own dynamics. The priority of the cognitive approach is emphasized in the methodological solutions proposed by many authors as methods of developing creative thinking. The authors also provide a psychological analysis of effective ways to develop adolescent creativity. It has been proven that the creative expression of adolescents is related to its general intellectual dynamics. Among the components that directly affect the creativity of adolescents: cognitive, emotional, practical, internal loci of control, behavioral scales, differences in gender were studied, and the results of the study were psychologically analyzed. The research results were processed using statistical methods and scientific conclusions and recommendations were developed.